DINAMIKA ETNIS MUSLIM ROHINGYA DI INDONESIA PASCA PENGUSIRAN DARI WILAYAH MYANMAR 2017-2024 - Dita Puji Rahayu; Nurrohim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research focuses on the social, economic and cultural dynamics of the Rohingya ethnicity in Indonesia after the expulsion from Myanmar in 2017. The purpose of this research is to analyze the living conditions of Rohingya refugees and the challenges and opportunities of their integration in Indonesia. The method used is qualitative with a descriptive-analytical approach through documentation studies of NGO reports, news, and academic literature. The results show that Rohingya refugees face various challenges, such as unclear legal status, limited access to education and employment, and social discrimination, despite solidarity from local communities and NGO assistance. Their cultural identity is negotiated between preserving tradition and adapting to local culture. Inclusive policies from the government, NGO support, and international collaboration are needed to improve the welfare and integration of Rohingya refugees in Indonesia.